2018
DOI: 10.1038/s41426-018-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of lysine 182 inhibits the ability of Mycobacterium tuberculosis DosR to bind DNA and regulate gene expression during hypoxia

Abstract: The DosR regulon is believed to be a key factor in latency adaptation of Mycobacterium tuberculosis and is strongly induced by multiple stresses, including hypoxia. Previous studies have revealed reversible acetylation of the conserved core DNA-binding lysine residue 182 (K182) of DosR in M. tuberculosis. In this study, we demonstrated that acetylated K182 plays an important role in the DNA-binding ability of DosR and that acetylation of K182 completely abolished the affinity of DosR for DNA in vitro. Antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
(66 reference statements)
3
21
0
Order By: Relevance
“…In the absence of cation binding and thiol redox switch, the mode of transcriptional regulation of Rv0081 in response to hypoxic conditions therefore remains enigmatic. Based on previous studies we can hypothesize that under hypoxic conditions, the Rv0081 might get post‐translationally modified to alter its DNA‐binding ability by phosphorylation , acetylation , methylation or modulation by formylation . First, to check the possibility of phosphorylation of Rv0081, three Serines which are postulated to be involved in base‐recognition become excellent candidates to test this hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of cation binding and thiol redox switch, the mode of transcriptional regulation of Rv0081 in response to hypoxic conditions therefore remains enigmatic. Based on previous studies we can hypothesize that under hypoxic conditions, the Rv0081 might get post‐translationally modified to alter its DNA‐binding ability by phosphorylation , acetylation , methylation or modulation by formylation . First, to check the possibility of phosphorylation of Rv0081, three Serines which are postulated to be involved in base‐recognition become excellent candidates to test this hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DNA‐binding properties of Rv0081 might be metal independent. In Mtb, metal‐independent DNA binding is regulated by either thiol switch or post‐transcriptional modifications, such as phosphorylation , acetylation or methylation and we can postulate one or combination of such mechanisms regulates the activity of Rv0081. With the emerging significance of Rv0081 in dormancy and our own observation of its indirect dependence on GroEL , we have determined the crystal structure of Rv0081 and identified the possible molecular basis for binding of Rv0081 to its cognate DNA element.…”
mentioning
confidence: 99%
“…It has recently been shown that hypoxia regulon of RR DosR, which is modulated by phosphorylation ( Saini et al, 2004 ; Sharma et al, 2019 ), is also regulated by its acetylation ( Bi et al, 2018 ; Yang et al, 2018 ). The study proposes that acetylation is reduced during hypoxia, which increases its DNA binding ability and thereby turns on the dormancy regulon ( Bi et al, 2018 ; Yang et al, 2018 ). These findings are in sync with the work presented here, in which (i) reduced DNA binding for MtrA is recorded when it is acetylated, and (ii) a regulatory effect of acetylation on the tuning growth of mycobacteria through acetylation of MtrA protein is demonstrated in both in vitro and in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, it is shown that the acetylation of RRs (TcrX and MtrA) affects their interaction with SKs, thus, tuning the fidelity of the SK-to-RR phosphotransfer reaction ( Singh et al, 2019 ). In the other report, deacetylation of the DosR response regulator is shown to promote the hypoxia response in Mtb , resulting in much lower infection in mice ( Bi et al, 2018 ; Yang et al, 2018 ). Based on the scheme of reactions in the TCS signaling process, the effect of acetylation of RR could be recorded at three distinct steps, (i) interaction of SK and RR proteins, (ii) phosphotransfer reaction from SK to RR, and (iii) DNA (or RNA) binding activity of the RR protein.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation